Arms and Armour in Ancient and Medieval Tibetan Literature - Maurer, Petra (Edizioni Ca’ Foscari, 2021)
This article presents Tibetan terms and expressions for arms and armour originating in Tibetan sources as per research conducted for the Wörterbuch der Tibetischen Schriftsprache, a dictionary database that includes sources ranging from the eight to the nineteenth centuries. This survey shows that Tibetan literature bears testimony to the existence of a broad variety of arms and armour in Tibet, which are mentioned in various contexts: Bon or Buddhist sources, historiographical or mythical accounts. By tracing these terms’ etymological origins and focusing on the actual use of weapons, we may gain a clearer understanding of the origin, use, and value of arms and armour in Tibetan culture.